Challenges in the Diagnosis and Management of Acquired Nontraumatic Urethral Strictures in Boys in Yaoundé, Cameroon - F. F. Mouafo Tambo; G. Fossi kamga; C. Kamadjou; L. Mbouche; A. S. Nwaha Makon; J. Birraux; O. G. Andze; F. F. Angwafo; P. Y. Mure (Case Reports in Urology)
Introduction. Urethral strictures in boys denote narrowing of the urethra which can be congenital or acquired. In case of acquired strictures, the etiology is iatrogenic or traumatic and rarely infectious or inflammatory. The aim of this study was to highlight the diagnostic and therapeutic difficulties of acquired nontraumatic urethral strictures in boys in Yaoundé, Cameroon. Methodology. The authors report five cases of nontraumatic urethral strictures managed at the Pediatric Surgery Department of the YGOPH over a two-year period (November 2012–November 2014). In order to confirm the diagnosis of urethral stricture, all patients were assessed with both cystourethrography and urethrocystoscopy. Results. In all the cases the urethra was inflammatory with either a single or multiple strictures. The surgical management included internal urethrotomy (n=1), urethral dilatation (n=1), vesicostomy (n=2), and urethral catheterization (n=3). With a median follow-up of 8.2 months (4–16 months) all patients remained symptoms-free. Conclusion. The authors report the difficulties encountered in the diagnosis and management of nontraumatic urethral strictures in boys at a tertiary hospital in Yaoundé, Cameroon. The existence of an inflammatory etiology of urethral strictures in boys deserves to be considered.